Ribose cross-linked collagen fiber and preparation and application thereof

CN118241483BActive Publication Date: 2026-10-27BEIJING AIBAIRUI BIOTECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410361029.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-27
Publication Date
2026-10-27
Estimated Expiration
2044-03-27

Smart Images

  • Figure BDA0004762733420000041
    Figure BDA0004762733420000041
  • Figure BDA0004762733420000042
    Figure BDA0004762733420000042
Patent Text Reader

Abstract

The present application provides a kind of ribose crosslinking collagen fiber, which is crosslinked by collagen fiber with ribose as crosslinking agent, the diameter of the collagen fiber is between 15-80nm; the diameter of the ribose crosslinking collagen fiber is between 150-200nm; the crosslinking degree of the ribose crosslinking collagen fiber is between 40.7%-56.1%; Tm value=58.54℃-66.46℃. The present application also provides a preparation method and application of the above-mentioned ribose crosslinking collagen fiber. The ribose crosslinking collagen fiber provided by the present application has lower thrust and resistance to collagenase degradation. The crosslinking agent used in the present application is natural ribose without any toxic side effects, which has better biocompatibility compared to other crosslinking forms.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a ribose-crosslinked collagen fiber, its preparation, and its application. Background Technology

[0002] As we age, the amount of collagen in our bodies gradually decreases, leading to problems such as sagging skin, increased wrinkles, and joint pain. Therefore, how to replenish collagen has always been a focus in the beauty and health care fields. High-purity animal-derived collagen has good biocompatibility and can be used as a tissue filler. However, due to the presence of collagenases in the body, clinical use has shown that natural collagen only lasts for 3-6 months in vivo. To increase the retention time of collagen fillers in the body, glutaraldehyde, reducing sugars, epoxide cross-linking agents, and imine cross-linking agents have been used to cross-link collagen to prepare more stable collagen fillers with a longer retention time in the body. The earliest cross-linked collagen filler products used in clinical wrinkle removal... Collagen implants and the already approved cross-linked collagen product "Fulimei" from Shuangmei Technology Co., Ltd. use glutaraldehyde as a cross-linking agent. Another approved cross-linked collagen filler product is the one developed by Col Bar Life Science Ltd., which uses ribose as a cross-linking agent. Other types of cross-linking agents currently lack approved products, and their biosafety requires further verification through clinical trials. A common characteristic of these products is that they first prepare collagen fibers through fibrillation under neutral conditions, followed by a cross-linking reaction. Reducing sugar cross-linking mimics the cross-linking stabilization reaction of collagen fibers caused by the interaction between collagen fibers and reducing glucose under physiological conditions. A Schiff base is formed between the reducing sugar and the ε-amino groups on the lysine and hydroxylysine residues of the collagen fiber. The Schiff base undergoes Amadori rearrangement and a series of further reactions to form irreversible and stable cross-links between collagen molecules. Because ribose cross-linking agents are natural reducing sugars without any toxic side effects, they have better biocompatibility compared to other cross-linking forms. However, ribose cross-linking of collagen has low efficiency and a long reaction time (US 6,682,760 B2). We believe that by regulating the fibrillation process and the assembly and arrangement of collagen molecules, the cross-linking efficiency and resistance to collagenase degradation of ribose-crosslinked collagen fibers can be improved. Summary of the Invention

[0003] To improve the crosslinking efficiency and resistance to collagenase degradation of ribose-crosslinked collagen fibers, and to increase the degree of crosslinking and melting point of crosslinked collagen fibers, this invention provides a novel ribose-crosslinked collagen fiber that can be used as a filler.

[0004] As one aspect of the present invention, ribose-crosslinked collagen fibers are formed by crosslinking collagen fibers with ribose as a crosslinking agent; the diameter of the collagen fibers is between 15-80 nm; the diameter of the ribose-crosslinked collagen fibers is between 150-200 nm; the degree of crosslinking of the ribose-crosslinked collagen fibers is between 40.7%-56.1%, preferably 48.6%-56.1%; the melting point Tm value is 58.54℃-66.46℃, preferably 59.59℃-66.46℃.

[0005] In another aspect, the invention relates to a cross-linked collagen fiber filler containing the aforementioned ribose-cross-linked collagen fibers. The filler may also contain lidocaine.

[0006] As another aspect of the present invention, a method for preparing the above-mentioned cross-linked collagen filler is provided, characterized in that the method comprises: adjusting the protein concentration to 35 mg / mL and the lidocaine concentration to 0.2% using physiological saline, homogenizing and aseptically filling the homogenate into 1 mL syringes, and sealing.

[0007] As another aspect of the present invention, a method for preparing the above-mentioned ribose-crosslinked collagen fibers is provided, comprising:

[0008] Purified collagen molecules, free from immunogenicity and viruses, were fibrotic under acidic conditions and then cross-linked with ribose. The acidic conditions were pH 5.0-6.0 and the ribose concentration was 1%-5% (w:v).

[0009] As demonstrated by the embodiments of this invention, the collagen fibers prepared under acidic conditions exhibit small diameters and, after ribose cross-linking, possess excellent thermal stability and resistance to collagenase degradation, maintaining a relatively long degradation cycle. These combined properties allow the ribose-crosslinked collagen fibers prepared by this invention to be used as a filler in conjunction with lidocaine in fields such as plastic surgery. Furthermore, the ribose-crosslinked collagen fibers exhibit low thrust and good biocompatibility, ensuring product safety and suitability for injectable fillings. Detailed Implementation

[0010] This application was jointly developed by Beijing Aibairui Biotechnology Co., Ltd. and Beijing Bairen Medical Technology Co., Ltd.

[0011] During their experiments with existing technologies, the inventors discovered that collagen fibers prepared under neutral conditions have a large diameter. While ribose crosslinking agents can increase the melting point of collagen fibers and improve their resistance to collagenase degradation, the crosslinking reaction efficiency is low and the reaction time is long (US 6,682,760 B2). CN114288469A reports that collagen fibers prepared under neutral conditions are crosslinked with ribose and then double-crosslinked with carbodiimide to further increase the melting point of the crosslinked collagen fibers. However, double crosslinking reduces the biocompatibility of single-ribose crosslinked collagen fibers. CN108752604 describes dissolving collagen molecules (molecular weight 50,000-300,000) in an ionic solution by heating, regenerating by cooling, and then crosslinking with ribose to increase collagen solubility, shorten crosslinking time, and improve crosslinking efficiency. However, collagen is prone to denaturation after high-temperature ionic solution treatment, losing its functional activity. It is generally believed that collagen fibers formed under acidic conditions have a smaller diameter and cannot meet the requirements for use as a filler. However, through further experiments, the inventors were surprised to find that as long as the process of preparing collagen fibers under acidic conditions is controlled, the prepared collagen fibers can react uniformly with ribose to form covalent bonds, the reaction efficiency is improved, and the melting point and degree of cross-linking of ribose-crosslinked collagen fibers are significantly improved. After further processing, they can be used as fillers.

[0012] The neutral conditions referred to in this application are pH values ​​of 6.5-7.5, and the acidic conditions referred to in this application are pH values ​​of 5.0-6.0.

[0013] The collagen fibers referred to in this application are the products of collagen molecules after undergoing a phosphate and NaCl fibrillation reaction. Under neutral conditions, the reaction mainly consists of collagen fibers with a diameter of 80-200 nm, while under acidic conditions, the reaction mainly consists of collagen fibers with a diameter of 15-30 nm.

[0014] The ribose-crosslinked collagen fiber referred to in this application is the product obtained by centrifugation and washing of collagen fiber after a ribose crosslinking reaction.

[0015] The method for testing the melting point of the prepared ribose-crosslinked collagen fibers according to the present invention is as follows:

[0016] The ribose-crosslinked collagen fibers were quantitatively transferred into the test aluminum crucible of the differential scanning calorimeter, and then sealed in the differential scanning calorimeter. The temperature was increased by 10 K / min under a nitrogen atmosphere, and the scanning measurement was performed within the temperature range of 25℃-100℃.

[0017] The method for testing the degree of crosslinking of the prepared ribose-crosslinked collagen fibers according to the present invention is as follows:

[0018] Quantitatively transfer ribose-crosslinked collagen fibers to microcentrifuge tubes. Prepare 0.1M pH 8.5 NaHCO3 solution and 0.5% (v:v) TNBS solution. Add 1 mL of each solution sequentially to the ribose-crosslinked collagen fibers and react at 40℃ for 2 hours. After the reaction, add 3 mL of 6M HCl and react at 60℃ for 1.5 hours. After cooling to room temperature, add 5 mL of deionized water and mix well. Take 5 mL of the mixture, add ether, shake, allow to separate into layers, and remove the ether. Repeat the process three times with fresh ether. After the ether has completely evaporated, take 200 μL of the reaction solution and add 400 μL of deionized water. Mix well and measure the absorbance at 345 nm using a microplate reader. Subtract the absorbance of the blank group to obtain absorbance value A. Repeat the above steps with an equal amount of uncrosslinked collagen fibers to obtain absorbance value B. Calculate the degree of crosslinking of the ribose-crosslinked collagen fibers using the following formula:

[0019]

[0020] The method for in vitro collagenase degradation testing of the prepared ribose-crosslinked collagen fibers according to the present invention is as follows:

[0021] A quantitative amount of ribose-crosslinked collagen fibers was transferred to a microcentrifuge tube. A 50 mM pH 7.4 TES collagenase reaction buffer was prepared. The ribose-crosslinked collagen fibers were then suspended in TES solution to a concentration of 2-5 mg / ml. Collagenase solution was added based on the total amount of ribose-crosslinked collagen fibers at a ratio of 1.25 U / mg. The mixture was digested at 37°C for 24 hours. The sample was centrifuged, and the precipitate and supernatant were collected. The collagen content in the precipitate and supernatant was calculated by measuring the hydroxyproline content using a microplate reader. Referring to McPherson et al. (1986) Journal of Biomedical Material Research, 20:79-92, the in vitro collagenase degradation rate of ribose-crosslinked collagen fibers was calculated using the following formula:

[0022]

[0023] Example 1: Preparation of ribose-crosslinked collagen fibers under neutral conditions

[0024] (1) Pretreatment of animal-derived tissues (this step can be carried out with reference to existing technology): Take fresh pig skin tissue, scrape off the surface fat, soak it in acetone solution at room temperature for 16 hours, wash the treated material with deionized water 3-5 times to remove excess acetone, then put the material into 2.0M NaOH solution at room temperature, stir for 16 hours, after the treatment is completed, soak it in deionized water and wash the material until neutral to achieve degreasing and virus inactivation.

[0025] (2) Extraction (This step can be carried out with reference to existing technology): The cleaned material is placed in 0.5M acetic acid for crushing and homogenization. The homogenized tissue is then used for collagen molecule extraction at a ratio of 20:1 (tissue weight / pepsin weight), with the temperature controlled at 18℃ and the extraction time controlled by stirring for 72 hours. The extract is centrifuged to collect the supernatant, and after stirring evenly, it is clarified and filtered to control the turbidity to be less than 30, thus obtaining a crude collagen molecule extract.

[0026] (3) Ultrafiltration purification (this step can be carried out with reference to existing technology): Use a tangential flow system to ultrafilter the crude collagen molecule extract, concentrate it to 3mg / ml, and then start dialyzing with 20mM acetic acid solution. After dialyzing 20 times the volume, collagen molecules are obtained.

[0027] (4) Collagen fibrosis: Take a certain volume of purified collagen molecules and add 1 / 10 volume of phosphate buffer (0.2M Na2HPO4:0.2M NaH2PO4 = 7:3, v:v). Mix well, adjust the pH to 7.0, and incubate at 30℃ for 6 hours to obtain collagen fibers. 90% of the collagen fibers have a diameter between 80-200 nm.

[0028] (5) Collagen fiber crosslinking: After centrifuging the collagen fibers to obtain a precipitate, add 10 times the volume of 0.5% (w:v) D-ribose-phosphate buffer, mix well, and incubate at 37°C with stirring for 15 days. Centrifuge to collect the precipitate, and wash three times with pH 7.0 phosphate buffer to obtain ribose-crosslinked collagen fibers. 70% of the ribose-crosslinked collagen fibers have a diameter between 150-200 nm and form a network structure.

[0029] (6) Filling: Take a certain volume of ribose cross-linked collagen fiber, centrifuge at 8000 rpm for 30 min, add physiological saline to the precipitate and homogenize it, then adjust the concentration to 35 mg / ml, and then aseptically fill the ribose cross-linked collagen fiber with the adjusted concentration into a 1 mL syringe, seal it, and obtain ribose cross-linked collagen fiber filler.

[0030] The ribose-crosslinked collagen fibers obtained in this embodiment were analyzed using differential scanning calorimetry and an ELISA reader. The Tm value was 56.05℃, and the degree of crosslinking was 30.4%. The degradation rate after in vitro collagenase treatment was 85%. Further physical properties were tested using a push-pull testing machine: with a 27G needle and a testing speed of 1 mL / min, the push force was 6.13 N.

[0031] Example 2: Preparation of ribose-crosslinked collagen fibers under neutral conditions

[0032] Steps (1)-(3) are the same as in Example 1.

[0033] (4) Collagen fibrosis: Take a certain volume of purified collagen molecules and add 1 / 10 volume of phosphate buffer (0.2M Na2HPO4:0.2M NaH2PO4 = 7:3, v:v). Mix well, adjust the pH to 7.0, and incubate at 30℃ for 6 hours to obtain collagen fibers. 90% of the collagen fibers have a diameter between 80-200 nm.

[0034] (5) Collagen fiber crosslinking: After centrifuging the collagen fibers to obtain a precipitate, add 10 volumes of 1% (w:v) D-ribose-phosphate buffer, mix well, and incubate at 37°C with stirring for 15 days. Centrifuge to collect the precipitate, and wash three times with pH 7.0 phosphate buffer to obtain ribose-crosslinked collagen fibers. 80% of the ribose-crosslinked collagen fibers have a diameter between 150-200 nm and form a network structure.

[0035] Step (6) is the same as in Example 1.

[0036] The ribose-crosslinked collagen fibers obtained in this embodiment were analyzed using differential scanning calorimetry and an ELISA reader. The Tm value was 56.68℃, and the degree of crosslinking was 31.2%. The degradation rate after in vitro collagenase treatment was 82%. Further physical properties were tested using a push-pull testing machine: with a 27G needle and a testing speed of 1 mL / min, the push force was 6.26 N.

[0037] Example 3: Preparation of ribose-crosslinked collagen fibers under neutral conditions

[0038] Steps (1)-(3) are the same as in Example 1.

[0039] (4) Collagen fibrosis: Take a certain volume of purified collagen molecules and add 1 / 10 volume of phosphate buffer (0.2M Na2HPO4:0.2M NaH2PO4 = 7:3, v:v). Mix well, adjust the pH to 7.0, and incubate at 30℃ for 6 hours to obtain collagen fibers. 90% of the collagen fibers have a diameter between 80-200 nm.

[0040] (5) Collagen fiber crosslinking: After centrifuging the collagen fibers to obtain a precipitate, add 10 times the volume of 3% (w:v) D-ribose-phosphate buffer, mix well, and incubate at 37°C with stirring for 15 days. Centrifuge to collect the precipitate, and wash three times with pH 7.0 phosphate buffer to obtain ribose-crosslinked collagen fibers. 90% of the ribose-crosslinked collagen fibers have a diameter between 150-200 nm and form a network structure.

[0041] Step (6) is the same as in Example 1.

[0042] The ribose-crosslinked collagen fibers obtained in this embodiment were analyzed using differential scanning calorimetry and an ELISA reader. The Tm value was 57.28℃, and the degree of crosslinking was 34%. The degradation rate after in vitro collagenase treatment was 73%. Further physical properties were tested using a push-pull testing machine: with a 27G needle and a testing speed of 1 mL / min, the push force was 6.89 N.

[0043] Example 4: Preparation of ribose-crosslinked collagen fibers under neutral conditions

[0044] Steps (1)-(3) are the same as in Example 1.

[0045] Collagen fibrosis: A certain volume of purified collagen molecules was taken and added to 1 / 10 volume of phosphate buffer (0.2M Na2HPO4:0.2M NaH2PO4 = 7:3, v:v). The mixture was stirred, the pH was adjusted to 7.0, and the mixture was incubated at 30°C for 6 hours to obtain collagen fibers. 90% of the collagen fibers had a diameter between 80-200 nm.

[0046] (5) Collagen fiber crosslinking: After centrifuging the collagen fibers to obtain a precipitate, add 10 times the volume of 5% (w:v) D-ribose-phosphate buffer, mix well, and incubate at 37°C with stirring for 15 days. Centrifuge to collect the precipitate, and wash three times with pH 7.0 phosphate buffer to obtain ribose-crosslinked collagen fibers. 90% of the ribose-crosslinked collagen fibers have a diameter between 150-200 nm and form a network structure.

[0047] Step (6) is the same as in Example 1.

[0048] The ribose-crosslinked collagen fibers obtained in this embodiment were analyzed using differential scanning calorimetry and an ELISA reader. The Tm value was 56.76℃, and the degree of crosslinking was 32.8%. The degradation rate after in vitro collagenase treatment was 75%. Further physical properties were tested using a push-pull testing machine: with a 27G needle and a testing speed of 1 mL / min, the push force was 6.43 N.

[0049] Example 5: Preparation of ribose-crosslinked collagen fibers under acidic conditions

[0050] Steps (1)-(3) are the same as in Example 1.

[0051] (4) Collagen fibrosis: Take a certain volume of purified collagen molecules and add 1 / 10 volume of phosphate buffer (0.2M Na2HPO4:0.2M NaH2PO4 = 7:3, v:v). Mix well, adjust the pH to 6.0, and incubate at 30℃ for 6 hours to obtain collagen fibers. 70% of the collagen fibers have a diameter of 50-80 nm.

[0052] (5) Collagen fiber crosslinking: After centrifuging the collagen fibers to obtain a precipitate, add 10 volumes of 1% (w:v) D-ribose-phosphate buffer, mix well, and incubate at 37°C with stirring for 15 days. Centrifuge to collect the precipitate, and wash three times with pH 7.0 phosphate buffer to obtain ribose-crosslinked collagen fibers. 80% of the ribose-crosslinked collagen fibers have a diameter between 150-200 nm and form a network structure.

[0053] Step (6) is the same as in Example 1.

[0054] The ribose-crosslinked collagen fibers obtained in this embodiment were analyzed using differential scanning calorimetry and an ELISA reader. The Tm value was 58.54℃, and the degree of crosslinking was 40.7%. The degradation rate after in vitro collagenase treatment was 58%. Further physical properties were tested using a push-pull testing machine: with a 27G needle and a testing speed of 1 mL / min, the push force was 5.68 N.

[0055] Example 6: Preparation of ribose-crosslinked collagen fibers under acidic conditions

[0056] Steps (1)-(3) are the same as in Example 1.

[0057] (4) Collagen fibrosis: Take a certain volume of purified collagen molecules and add 1 / 10 volume of phosphate buffer (0.2M Na2HPO4:0.2M NaH2PO4 = 7:3, v:v). Mix well, adjust the pH to 5.0, and incubate at 30℃ for 6 hours to obtain collagen fibers. 70% of the collagen fibers have a diameter of 15-30 nm.

[0058] (5) Collagen fiber crosslinking: After centrifuging the collagen fibers to obtain a precipitate, add 10 volumes of 1% (w:v) D-ribose-phosphate buffer, mix well, and incubate at 37°C with stirring for 15 days. Centrifuge to collect the precipitate, and wash three times with pH 7.0 phosphate buffer to obtain ribose-crosslinked collagen fibers. 80% of the ribose-crosslinked collagen fibers have a diameter between 150-200 nm and form a network structure.

[0059] Step (6) is the same as in Example 1.

[0060] The ribose-crosslinked collagen fibers obtained in this embodiment were analyzed using differential scanning calorimetry and an ELISA reader. The Tm value was 59.12℃, and the degree of crosslinking was 46.9%. The degradation rate after in vitro collagenase treatment was 56%. Further physical properties were tested using a push-pull testing machine: with a 27G needle and a testing speed of 1 mL / min, the push force was 4.12 N.

[0061] Example 7: Preparation of ribose-crosslinked collagen fibers under acidic conditions

[0062] Steps (1)-(3) are the same as in Example 1.

[0063] (4) Collagen fibrosis: Take a certain volume of purified collagen molecules, add 1 / 10 volume of phosphate buffer (0.2M Na2HPO4:0.2M NaH2PO4 = 7:3, v:v), then add 0.15M NaCl, mix well and adjust the pH to 5.0. Incubate at 30℃ for 6 hours to obtain collagen fibers. 90% of the collagen fibers have a diameter of 15-30 nm.

[0064] (5) Collagen fiber crosslinking: After centrifuging the collagen fibers to obtain a precipitate, add 10 volumes of 1% (w:v) D-ribose-phosphate buffer, mix well, and incubate at 37°C with stirring for 15 days. Centrifuge to collect the precipitate, and wash three times with pH 7.0 phosphate buffer to obtain ribose-crosslinked collagen fibers. 80% of the ribose-crosslinked collagen fibers have a diameter between 150-200 nm and form a network structure.

[0065] Step (6) is the same as in Example 1.

[0066] The ribose-crosslinked collagen fibers obtained in this embodiment were analyzed using differential scanning calorimetry and an ELISA reader. The Tm value was 62.09℃, and the degree of crosslinking was 54.3%. The degradation rate after in vitro collagenase treatment was 42%. Further physical properties were tested using a push-pull testing machine: with a 27G needle and a testing speed of 1 mL / min, the push force was 4.32 N.

[0067] Example 8: Preparation of ribose-crosslinked collagen fibers under acidic conditions

[0068] Steps (1)-(3) are the same as in Example 1.

[0069] (4) Collagen fibrosis: Take a certain volume of purified collagen molecules, add 1 / 10 volume of phosphate buffer (0.2M Na2HPO4:0.2M NaH2PO4 = 7:3, v:v), then add 0.15M NaCl, mix well and adjust the pH to 5.0. Incubate at 30℃ for 6 hours to obtain collagen fibers. 90% of the collagen fibers have a diameter of 15-30 nm.

[0070] (5) Collagen fiber crosslinking: After centrifuging the collagen fibers to obtain a precipitate, add 10 volumes of 1% (w:v) D-ribose-phosphate buffer, mix well, and incubate at 37°C with stirring for 12 days. Centrifuge to collect the precipitate, and wash three times with pH 7.0 phosphate buffer to obtain ribose-crosslinked collagen fibers. 80% of the ribose-crosslinked collagen fibers have a diameter between 150-200 nm and form a network structure.

[0071] Step (6) is the same as in Example 1.

[0072] The ribose-crosslinked collagen fibers obtained in this embodiment were analyzed using differential scanning calorimetry and an ELISA reader. The Tm value was 60.74℃, and the degree of crosslinking was 52%. The degradation rate after in vitro collagenase treatment was 49%. Further physical properties were tested using a push-pull testing machine: with a 27G needle and a testing speed of 1 mL / min, the push force was 3.87 N.

[0073] Example 9: Preparation of ribose-crosslinked collagen fibers under acidic conditions

[0074] Steps (1)-(3) are the same as in Example 1.

[0075] (4) Collagen fibrosis: Take a certain volume of purified collagen molecules, add 1 / 10 volume of phosphate buffer (0.2M Na2HPO4:0.2M NaH2PO4 = 7:3, v:v), then add 0.15M NaCl and mix well to adjust the pH to 5.0. Incubate at 30℃ for 6 hours to obtain collagen fibers. 90% of the collagen fibers have a diameter of 15-30 nm.

[0076] (5) Collagen fiber crosslinking: After centrifuging the collagen fibers to obtain a precipitate, add 10 volumes of 1% (w:v) D-ribose-phosphate buffer, mix well, and incubate at 37°C with stirring for 10 days. Centrifuge to collect the precipitate, and wash three times with pH 7.0 phosphate buffer to obtain ribose-crosslinked collagen fibers. 80% of the ribose-crosslinked collagen fibers have a diameter between 150-200 nm and form a network structure.

[0077] Step (6) is the same as in Example 1.

[0078] The ribose-crosslinked collagen fibers obtained in this embodiment were analyzed using differential scanning calorimetry and an ELISA reader. The Tm value was 59.59℃, and the degree of crosslinking was 48.6%. The degradation rate after in vitro collagenase treatment was 55%. Further physical properties were tested using a push-pull testing machine: with a 27G needle and a testing speed of 1 mL / min, the push force was 3.74 N.

[0079] Example 10: Preparation of ribose-crosslinked collagen fibers under acidic conditions

[0080] Steps (1)-(3) are the same as in Example 1.

[0081] (4) Collagen fibrosis: Take a certain volume of purified collagen molecules, add 1 / 10 volume of phosphate buffer (0.2M Na2HPO4:0.2M NaH2PO4 = 7:3, v:v), then add 0.15M NaCl, mix well and adjust the pH to 5.0. Incubate at 30℃ for 6 hours to obtain collagen fibers. 90% of the collagen fibers have a diameter of 15-30 nm.

[0082] (5) Collagen fiber crosslinking: After centrifuging the collagen fibers to obtain a precipitate, add 10 times the volume of 3% (w:v) D-ribose-phosphate buffer, mix well, and incubate at 37°C with stirring for 10 days. Centrifuge to collect the precipitate, and wash three times with pH 7.0 phosphate buffer to obtain ribose-crosslinked collagen fibers. 90% of the ribose-crosslinked collagen fibers have a diameter between 150-200 nm and form a network structure.

[0083] Step (6) is the same as in Example 1.

[0084] The ribose-crosslinked collagen fibers obtained in this embodiment were analyzed using differential scanning calorimetry and an ELISA reader. The Tm value was 66.46℃, and the degree of crosslinking was 56.1%. The degradation rate after in vitro collagenase treatment was 39%. Further physical properties were tested using a push-pull testing machine: with a 27G needle and a testing speed of 1 mL / min, the push force was 4.87 N.

[0085] Example 11: Preparation of ribose-crosslinked collagen fibers under acidic conditions

[0086] Steps (1)-(3) are the same as in Example 1.

[0087] (4) Collagen fibrosis: Take a certain volume of purified collagen molecules, add 1 / 10 volume of phosphate buffer (0.2M Na2HPO4:0.2M NaH2PO4 = 7:3, v:v), then add 0.15M NaCl, mix well and adjust the pH to 5.0. Incubate at 30℃ for 6 hours to obtain collagen fibers. 90% of the collagen fibers have a diameter of 15-30 nm.

[0088] (5) Collagen fiber crosslinking: After centrifuging the collagen fibers to obtain a precipitate, add 10 times the volume of 5% (w:v) D-ribose-phosphate buffer, mix well, and incubate at 37°C with stirring for 10 days. Centrifuge to collect the precipitate, and wash three times with pH 7.0 phosphate buffer to obtain ribose-crosslinked collagen fibers. 90% of the ribose-crosslinked collagen fibers have a diameter between 150-200 nm and form a network structure.

[0089] Step (6) is the same as in Example 1.

[0090] The ribose-crosslinked collagen fibers obtained in this embodiment were analyzed using differential scanning calorimetry and an ELISA reader. The Tm value was 59.71℃, and the degree of crosslinking was 50.2%. The degradation rate after in vitro collagenase treatment was 47%. Further physical properties were tested using a push-pull testing machine: with a 27G needle and a testing speed of 1 mL / min, the push force was 5.56 N.

[0091] In the above embodiments, steps (1)-(3) are the same, mainly involving defatting and virus-killing of the material, and extraction and purification of collagen molecules. Step (4) involves fibrillating the purified collagen molecules, and step (5) involves ribose crosslinking of the collagen fibers. In Examples 1-4, fibrillation was performed under neutral conditions at pH 7.0, followed by crosslinking treatment with 0.5%, 1%, 2%, and 5% D-ribose-phosphate buffer for 15 days. In Examples 5 and 6, fibrillation was performed under acidic conditions at pH 6.0 and pH 5.0, followed by crosslinking treatment with 1% D-ribose-phosphate buffer for 15 days. Examples 7-11 used acidic conditions (pH 5.0) for fibrosis treatment, and added NaCl to the fibrosis reaction solutions: Na2HPO4 and NaH2PO4 solutions. Then, cross-linking treatment was carried out using D-ribose-phosphate buffer solutions of different concentrations. In Examples 7-9, 1% ribose was used for cross-linking for 15, 12, and 10 days; in Examples 9-11, 1%, 3%, and 5% ribose were used for cross-linking for 10 days.

[0092] The melting point, degree of crosslinking, degradation rate, and thrust of the ribose-crosslinked collagen fibers obtained in all examples were measured. Examples 1-3 show that with increasing ribose concentration, the melting point and degree of crosslinking of the ribose-crosslinked collagen fibers increase, while the collagenase degradation rate decreases. However, Example 4 shows that with further increases in ribose concentration, the degree of crosslinking and resistance to collagenase degradation decrease, consistent with the change in degradation rate with concentration after fiberization under neutral conditions described in US 6682769. Examples 2, 5, and 6 show that the thermal stability, degree of crosslinking, and resistance to collagenase degradation of ribose-crosslinked collagen fibers obtained under low-concentration ribose and acidic conditions increase with decreasing pH compared to ribose-crosslinked collagen fibers obtained under neutral conditions, while the thrust decreases with decreasing reaction pH. Examples 7, 8, and 9 show that adding NaCl to the fiberization reaction solution (Na2HPO4 and NaH2PO4) under acidic conditions is beneficial for fiber formation under acidic conditions, and high-melting-point and high-degree-of-crosslinking ribose-crosslinked collagen fibers can still be obtained by reducing the crosslinking time. Examples 9, 10, and 11 demonstrate that reducing the crosslinking time while increasing the ribose concentration can increase the degree of crosslinking and the Tm value of ribose-crosslinked collagen fibers, thereby improving their resistance to collagenase degradation. In particular, the ribose-crosslinked collagen fibers obtained in Example 10 showed the best results; single-stage ribose crosslinking of collagen fibers under acidic conditions was comparable to the effect of dual crosslinking with ribose and carbodiimide reported in CN114288469A. They exhibited good thermal stability at Tm = 66.64℃ and a crosslinking degree of 56.1%, with significantly improved resistance to collagenase degradation; a pushing force of 4.87 N, which is more conducive to injection filling; and a shortened ribose crosslinking reaction time, making them suitable for large-scale production.

[0093] Collagen fibers prepared under neutral conditions have a larger diameter, and the degree of cross-linking of the prepared ribose-crosslinked collagen fibers is between 30.4% and 34%, with a Tm value of 56.05℃-57.28℃. Although this improves the maintenance time of collagen fibers as fillers to some extent, the resistance to collagenase degradation still does not meet expectations. Experiments have shown that regulating the fibrillation process and the assembly and arrangement of collagen molecules can improve the cross-linking efficiency and resistance to collagenase degradation. Collagen fibers with smaller diameters prepared under acidic conditions can react fully and uniformly with the cross-linking agent, thereby improving the degree of cross-linking and melting point. The ribose-crosslinked collagen fibers prepared in this invention have a cross-linking degree between 40.7% and 56.1%, preferably 48.6%-56.1%, which improves the resistance to collagenase degradation; the melting point Tm value is 58.54℃-66.46℃, preferably 59.59.59℃-66.46℃, which shows good thermal stability and corresponds to a longer degradation cycle. The combined effect of these properties allows the ribose-crosslinked collagen fibers prepared by this invention to be used as fillers in conjunction with lidocaine in fields such as plastic surgery. Moreover, the crosslinked collagen fiber fillers prepared with natural ribose as a crosslinking agent have low thrust, which greatly improves the biocompatibility and effectiveness of the fillers.

Claims

1. A method for preparing ribose-crosslinked collagen fibers, characterized in that, include: Pig skin tissue was pretreated, extracted, and purified to obtain purified collagen molecules free of immunogenicity and viruses. Then, phosphate buffer (1 / 10 volume of 0.2M Na₂HPO₄ and 0.2M NaH₂PO₄ in a 7:3 volume ratio) and 0.15M NaCl were added. After fibrinization under acidic conditions, ribose cross-linking was performed. The ribose concentration was 1%-5%; the pH of the acidic conditions was 5.

0. The ribose-crosslinked collagen fibers were formed by cross-linking collagen fibers with ribose as the cross-linking agent. The diameter of the collagen fibers was between 15-80 nm; the diameter of the ribose-crosslinked collagen fibers was between 150-200 nm; the degree of cross-linking of the ribose-crosslinked collagen fibers was between 40.7%-56.1%; and the Tm value was 58.54℃-66.46℃.

2. The method for preparing ribose-crosslinked collagen fibers according to claim 1, characterized in that, The degree of cross-linking of the ribose-crosslinked collagen fibers is between 48.6% and 56.1%; the Tm value is between 59.59℃ and 66.46℃.

3. The method for preparing ribose-crosslinked collagen fibers according to claim 2, characterized in that, The degree of cross-linking of the ribose-crosslinked collagen fiber is 56.1%; Tm value = 66.46℃.

4. The method according to claim 3, characterized in that, The acidic condition is phosphate buffer, the collagen molecules are animal-derived collagen molecules, and the ribose is D-ribose.

5. A cross-linked collagen fiber filler, characterized in that, The filler comprises ribose-crosslinked collagen fibers obtained by any of the methods described in claims 1-4.

6. The cross-linked collagen fiber filler according to claim 5, characterized in that, The filler also contains lidocaine.

7. A method for preparing the cross-linked collagen filler according to claim 6, characterized in that, The method includes: adjusting the protein concentration to 35 mg / mL and the lidocaine concentration to 0.2% using physiological saline, homogenizing the mixture, aseptically filling it into 1 mL syringes, and sealing it.

Citation Information

Patent Citations

  • Composition, preparation method and application of dual-crosslinking collagen filler

    CN114288469A

  • Cross-linked collagen matrices and methods for their preparation

    US6682760B2

  • Noodle loosening promoter and method for its production

    US6682769B2

  • Collagen for injection, preparation method and filling agent

    CN107308494A

  • Collagen-synthetic polymer conjugates having controlled fiber size distributions

    EP0668081A2